La relación entre los estudios y la formación de usuarios de la información - Hernández Salazar, Patricia (Revista General de Información y Documentación, 2008)
One of the educational and investigating preoccupations of most academics of a disciplinary area is to find the bonds between the discipline subfields, these bonds represent the conceptual relations that conform a theoretical frame. The community of librarianship and information sciences pretends create their theoretical frame, concretely in the users area. In this area two subjects exist that must be intimately bound, the user studies and the user formation (education). The objective of this paper is to establish the relationship between user studies and user formation (education), to accomplish it both processes are defined and categorized. Also, three user studies are described and related to user formation (education). The user studies were focused on university communities.